Humidifying laminate and humidifier
By using porous enhanced materials and perforated membrane layer stacked structures in the humidifier, the existing humidifier's limits of miniaturization and cost reduction are solved, and the effect of high humidity and miniaturization is achieved.
Patent Information
- Application Number
- CN202380045957.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-15
- Filing Date
- 2023-06-12
- Publication Date
- 2025-01-21
AI Technical Summary
Existing moisture permeable film humidifiers have limits in miniaturization and cost reduction, and moisture permeability is reduced by the increase in film thickness required for the concave and convex shape.
The porous enhanced material and the non -porosal membrane layer are used as a humidized membrane. It improves the humidity performance through high water protection and adsorption capacity of porous membranes and the adsorption capacity of porous materials, and realizes the miniaturization of the humidifier.
Improve the moisture permeability, realize the miniaturization of the humidifier, avoid moisture resistance, and maintain efficient humidification performance.
Smart Images

Figure CN119343233A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a humidifying laminate and a humidifier. In addition, this application claims priority to Japanese Patent Application No. 2022-096876 filed in Japan on June 15, 2022, the contents of which are incorporated herein by reference. Background Art
[0002] As a humidifier, a moisture permeable membrane humidifier that can achieve both ventilation and humidification is known. However, such a moisture permeable membrane humidifier has a problem of increased cost, although it has higher humidification performance than a natural evaporation humidifier that supplies water to the surface of an evaporation plate to humidify the air.
[0003] In order to reduce costs, research on reducing the number and size of components is being conducted. For example, as in Patent Document 1, a moisture permeable membrane type humidifier having a concavo-convex shape on the membrane surface in order to increase the surface area of the moisture permeable membrane has been studied.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2001-174008 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, in the invention described in Patent Document 1, the thickness of the moisture permeable membrane needs to be increased according to the size of the member for imparting the concavoconvex shape to the moisture permeable membrane. Therefore, there is a limit to the size reduction of the humidifier, and the cost reduction is also insufficient.
[0009] Furthermore, there is a problem that the film thickness of the moisture-permeable film needs to be increased more than necessary due to the uneven shape, which causes moisture permeation resistance and reduces the moisture permeability performance itself.
[0010] Therefore, an object of the present disclosure is to provide a humidifying laminate that can improve moisture permeability and reduce the size of a humidifier.
[0011] Solutions for solving problems
[0012] The inventors of the present disclosure have conducted intensive research to achieve the above-mentioned purpose, and as a result, have found that the moisture permeability can be improved and the humidifier can be miniaturized if the following humidification laminate has: a porous reinforcing material; and a non-porous film laminated on at least one surface of the porous reinforcing material to function as a moisture permeable film, wherein the moisture permeability of the laminate is greater than the moisture permeability of the porous reinforcing material alone. The present disclosure relates to a material completed based on these findings.
[0013] That is, the present disclosure provides a humidifying laminate, which is a laminate comprising: a porous reinforcing material; and a non-porous film laminated on at least one surface of the porous reinforcing material and functioning as a moisture-permeable film, wherein the moisture permeability of the laminate is greater than that of the porous reinforcing material alone.
[0014] The humidifying laminated body can exhibit sufficient moisture permeability even without providing a concavo-convex shape on the humidifying laminated body by using a nonporous film having a moisture permeability higher than that of the porous reinforcing material alone, and can reduce the size of the humidifier.
[0015] The nonporous film preferably has a property that the thicker the film is, the higher the moisture permeability is. By using such a nonporous film, the humidifying laminate can more easily exhibit moisture permeability.
[0016] The adsorption isotherm of the porous reinforcing material is preferably any one of types I to VI as shown in IUPAC.
[0017] Furthermore, the adsorption isotherm of the porous reinforcing material is preferably type III as indicated by IUPAC.
[0018] The adsorption isotherm of the nonporous membrane is preferably any one of types I to VI as shown in IUPAC.
[0019] Furthermore, the adsorption isotherm of the nonporous membrane is preferably type III as indicated by IUPAC.
[0020] The moisture content of the nonporous film at a relative humidity of 100% is preferably 10 times or more than that of the porous reinforcing material. By making the moisture content of the nonporous film at a relative humidity of 100% 10 times or more than that of the porous reinforcing material, the humidifying laminate can easily exhibit moisture permeability.
[0021] Furthermore, the non-porous membrane is preferably disposed on the water side of the liquid relative to the porous reinforcing material so as to absorb water from the liquid and release it into the air.
[0022] The cationic portion preferably contains a group containing an ammonium ion or a group capable of forming an ammonium ion. By containing a group containing an ammonium ion or a group capable of forming an ammonium ion, the nonporous membrane can exert a bactericidal effect, thereby inhibiting the adhesion / accumulation of miscellaneous bacteria and the like.
[0023] Preferably, the thermoplastic resin has a hydrophilic portion, and the hydrophilic portion contains a structural unit represented by the following formula (1). The nonporous membrane can form a water conduction path in the nonporous membrane due to the hydrophilic portion having the structural unit, and can easily exhibit moisture permeability.
[0024] [Chemical formula 1]
[0025]
[0026] (R 1 , R 2 independently represents a hydrogen atom or a methyl group. )
[0027] In addition, it is preferred that the thermoplastic resin has a hydrophobic portion, and the hydrophobic portion contains a structural unit represented by the following formula (2) and / or the following formula (3). The nonporous membrane can form a water-conducting path in the nonporous membrane by having the hydrophobic portion of the structural unit, and can easily exhibit moisture permeability.
[0028] [Chemical formula 2]
[0029]
[0030] (R 1 represents a hydrogen atom or a methyl group, R 3 represents a hydrogen atom or an alkyl group having 1 to 2 carbon atoms. )
[0031] [Chemical formula 3]
[0032]
[0033] (R 1 represents a hydrogen atom or a methyl group, R 4 represents a branched alkyl group having 3 or more carbon atoms.
[0034] Furthermore, in the humidifying laminate, it is preferred that the nonporous film is applied so as to cover at least one surface of the porous reinforcing material.
[0035] Furthermore, the present invention provides a humidifier provided with a plurality of bag-shaped water-retaining containers formed by bonding the above-mentioned humidifying laminate to a frame.
[0036] Furthermore, the present disclosure provides an air conditioner equipped with the above-mentioned humidifier.
[0037] Furthermore, the present disclosure provides a ventilation device equipped with the above-mentioned humidifier.
[0038] In addition, the present disclosure provides an air purifier equipped with the above-mentioned humidifier.
[0039] Beneficial Effects
[0040] The humidifying laminate of the present disclosure can improve the moisture permeability and downsize the humidifier. Therefore, the humidifying laminate of the present disclosure is preferably used in a moisture permeable membrane type humidifier. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a schematic cross-sectional view showing one embodiment of the humidification laminate of the present disclosure. DETAILED DESCRIPTION
[0042] [Laminate for humidification]
[0043] The humidifying laminate of one embodiment of the present disclosure at least has: a porous reinforcing material; and a non-porous membrane, which is provided on at least one surface of the porous reinforcing material. The non-porous membrane can be provided on a single side of the reinforcing material, or on both sides. In addition, the humidifying laminate can also be a structure in which the non-porous membrane is clamped by two of the porous reinforcing materials. That is, the porous reinforcing material can also be provided on both sides of the non-porous membrane. In this case, the two porous reinforcing materials can be the same porous reinforcing materials, or they can be porous reinforcing materials with different materials, thicknesses, etc.
[0044] Figure 1 1 is a schematic cross-sectional view showing one embodiment of the humidifying laminate of the present disclosure. The humidifying laminate 1 includes a porous reinforcing material 11 and a non-porous membrane 12 provided on one surface 11 a of the porous reinforcing material 11 .
[0045] <Non-porous membrane>
[0046] The non-porous film functions as a moisture permeable film. The humidifying laminate having the non-porous film on at least one surface of the porous reinforcing material has a moisture permeability higher than that of the porous reinforcing material alone. It is speculated that the reason is that the non-porous film has high water retention. Such a non-porous film does not need to be provided with a concave-convex shape in order to increase the surface area, and the structure of the humidifying laminate can be miniaturized. It should be noted that the moisture permeability is set based on the moisture permeability test method (cup method) of JIS Z0208-1976. Under the conditions of temperature 20°C, relative humidity 30%, wind speed 2.4m / s and temperature 20°C, relative humidity 65%, wind speed 0.1m / s, a moisture permeable cup in a state of adding 40g of water is set in a constant temperature and humidity chamber, and the reduction in the total mass of water and the moisture permeable cup after 1 hour is converted into the test piece per 1m 2 The mass after 24 hours is calculated as the moisture permeability.
[0047] Moreover, the non-porous film preferably has the property that the thicker the film thickness is, the more high moisture permeability is exerted. In a common moisture permeable film, moisture permeability resistance is generated due to the thickening of the film thickness, and the moisture permeability is reduced. On the other hand, it is inferred that the non-porous film has high water retention, so it does not cause moisture permeability resistance, and high moisture permeability can be exerted even if the film thickness is thickened.
[0048] The thickness of the nonporous film is preferably 0.5 μm to 5 μm, more preferably 1 μm to 4 μm. If the thickness is 0.5 μm or more, the film forming property becomes good, the gas barrier property can be improved, and the moisture permeability can be further improved. If the thickness is 5 μm or less, it is easy to form a thin film, sufficient moisture permeability can be maintained, and the humidifier can be miniaturized, and the economic efficiency is also excellent.
[0049] The adsorption isotherm of the nonporous membrane is preferably any one of type I to type VI shown by IUPAC, and more preferably type III. By making the adsorption isotherm of the nonporous membrane any one of type I to type VI shown by IUPAC, the water retention capacity of the nonporous membrane tends to increase, so the humidification laminated body is easy to exert moisture permeability.
[0050] The moisture content of the nonporous film at a relative humidity of 100% is preferably 2% or more, more preferably 2.5% or more, and particularly preferably 3% or more. When the moisture content of the nonporous film at a relative humidity of 100% is 2% or more, the humidifying laminate can easily exhibit moisture permeability.
[0051] In addition, the water content of the nonporous film at a relative humidity of 100% is preferably 10 times or more, more preferably 15 times or more, relative to the porous reinforcing material. By making the water content of the nonporous film at a relative humidity of 100% 10 times or more than the water content of the porous reinforcing material, the humidifying laminate can easily exhibit moisture permeability.
[0052] In addition, the non-porous film preferably comprises a thermoplastic resin, and the thermoplastic resin preferably has a cationic portion. Therefore, the non-porous film preferably has the cationic portion. By having the cationic portion, the non-porous film can exert a repulsive force on scale components that are usually mostly made of metal ions and have positive charges, and can inhibit the attachment / accumulation of scale components to the non-porous film.
[0053] In order to make the non-porous film absorb water, the thermoplastic resin preferably has a hydrophilic part. In addition, in order to form a water-conducting passage in the non-porous film, the thermoplastic resin preferably has a hydrophobic part. Therefore, the thermoplastic resin preferably has both a hydrophilic part and a hydrophobic part. It is speculated that: in the non-porous film, by forming a structure in which the hydrophilic part and the hydrophobic part are separated, the hydrophilic part functions as a water-conducting passage, allowing more water vapor to pass through, so that the moisture permeability is more excellent.
[0054] Examples of the thermoplastic resin include acrylic resins, cellulose resins, polyester resins such as polybutylene terephthalate, polyether resins, polyurethane resins, polyvinyl chloride resins, polyethylene, polystyrene resins, polyamide resins, polyacetal resins, polycarbonate resins, polyphenylene sulfide resins, polyetheretherketone, polyimide resins, polytetrafluoroethylene resins, polycaprolactone, and polylactic acid.
[0055] As described above, the thermoplastic resin preferably has a hydrophilic portion, a hydrophobic portion, and a cationic portion, and is therefore preferably a thermoplastic copolymer containing different monomer components.
[0056] The hydrophilic part is preferably composed of a monomer (a) (hereinafter referred to as monomer (a)) unit containing a hydrophilic functional group in a side chain in the structural unit of the copolymer. In addition, the hydrophobic part is preferably composed of a monomer (b) (hereinafter referred to as monomer (b)) unit containing a hydrophobic functional group in a side chain. In addition, the hydrophilic part and the hydrophobic part are preferably formed in the copolymer. In the non-porous film, the copolymer can maintain a core-shell structure in which the hydrophobic part is formed inside and the hydrophilic part is formed outside. In this case, the hydrophilic part and the hydrophobic part can be formed by the core and shell of two or more adjacent copolymers. In addition, the copolymer can also be a core-shell structure before the non-porous film is formed, and the core-shell structure is not maintained when the non-porous film is formed.
[0057] The copolymer preferably contains a structural unit derived from the monomer (a) as a part constituting the hydrophilic part. As the monomer (a), for example, there can be listed: a monomer containing a glycidyl group, a monomer containing a hydrolyzable silyl group, a monomer containing an acetoacetyl group, a monomer containing a hydroxyl group, a monomer containing a carboxyl group, methyl (meth)acrylate, and a monomer having a cationic functional group described later. Among them, preferably a monomer containing a carboxyl group, methyl (meth)acrylate, and a monomer having a cationic functional group described later. The monomer (a) can be used alone or in combination of two or more. It should be noted that "(meth)acrylic acid" in this specification means at least one of "acrylic acid" and "methacrylic acid".
[0058] As said glycidyl group-containing monomer, glycidyl (meth)acrylate, (meth)allyl glycidyl ether, etc. are mentioned, for example.
[0059] Examples of the hydrolyzable silyl group-containing monomer include vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy)silane, and vinyl methyl dimethoxysilane; and (meth) acryloxy silyl group-containing monomers such as γ-(meth)acryloxypropyl trimethoxysilane, γ-(meth)acryloxypropyl methyl dimethoxysilane, γ-(meth)acryloxypropyl triethoxysilane, and γ-(meth)acryloxypropyl methyl diethoxysilane.
[0060] Examples of the acetoacetyl group-containing monomer include allyl diacetoacetate, acetoacetoxyethyl (meth)acrylate, acetoacetoxyethyl crotonate, acetoacetoxypropyl (meth)acrylate, acetoacetoxypropyl crotonate, and 2-cyanoacetoacetoxyethyl (meth)acrylate.
[0061] Examples of the hydroxyl group-containing monomer include hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate.
[0062] Examples of the carboxyl group-containing monomer include acid anhydride monomers such as crotonic acid, maleic acid, and maleic anhydride, fumaric acid, citraconic acid, glutaconic acid, itaconic acid, acrylamide N-glycolic acid, cinnamic acid, and (meth)acrylic acid.
[0063] Furthermore, as the monomer (a), methyl (meth)acrylate and / or (meth)acrylic acid are particularly preferred. That is, the hydrophilic portion preferably includes a structural unit represented by the following formula (1).
[0064] [Chemical formula 1]
[0065]
[0066] (R 1 , R 2 Each independently represents a hydrogen atom or a methyl group. )
[0067] The content of the monomer (a) is preferably 20 to 70 mol%, more preferably 30 to 70 mol%, and further preferably 40 to 60 mol% relative to the total monomer components constituting the copolymer. By adjusting the content of the monomer (a) within this range, a hydrophilic portion can be formed in the nonporous membrane, and a water-conducting path can be easily formed, resulting in better moisture permeability.
[0068] The copolymer preferably contains a structural unit derived from the monomer (b) as a part constituting the hydrophobic portion. The monomer (b) is not particularly limited, but preferably contains a monomer having a hydrocarbon group with a carbon number of 2 or more, and more preferably, a (meth)acrylate having a hydrocarbon group with a carbon number of 2 or more can be cited. The monomer (b) can be used alone or in combination of two or more.
[0069] Examples of the hydrocarbon group having 2 or more carbon atoms include an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, an aromatic hydrocarbon group, and a group in which two or more of these are bonded to each other.
[0070] Examples of the aliphatic hydrocarbon group include alkyl, alkenyl, and alkynyl. Examples of the alkyl group include straight or branched alkyl groups such as ethyl, propyl, isopropyl, butyl, isobutyl, hexyl, octyl, isooctyl, decyl, dodecyl, and stearyl. Examples of the alkenyl group include straight or branched alkenyl groups such as vinyl, allyl, methallyl, 1-propenyl, isopropenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, and 5-hexenyl. Examples of the alkynyl group include straight or branched alkynyl groups such as ethynyl and propynyl.
[0071] Examples of the alicyclic hydrocarbon group include cycloalkyl groups having 3 to 12 carbon atoms such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl and cyclododecyl; cycloalkenyl groups having 3 to 12 carbon atoms such as cyclohexenyl; and bridged hydrocarbon groups having 4 to 15 carbon atoms such as bicycloheptyl and bicycloheptenyl.
[0072] Examples of the aromatic hydrocarbon group include aryl groups having 6 to 14 carbon atoms (particularly aryl groups having 6 to 10 carbon atoms), such as phenyl and naphthyl.
[0073] The hydrocarbon group having 2 or more carbon atoms is preferably an aliphatic hydrocarbon group or an aromatic hydrocarbon group, and more preferably a linear or branched alkyl group or an aromatic hydrocarbon group.
[0074] Specifically, the monomer (b) is preferably a monomer capable of forming a structural unit represented by the following formula (2) and / or the following formula (3). That is, the hydrophobic portion preferably includes a structural unit represented by the following formula (2) and / or the following formula (3).
[0075] [Chemical formula 2]
[0076]
[0077] (R 1 represents a hydrogen atom or a methyl group, R 3 represents a hydrogen atom or an alkyl group having 1 to 2 carbon atoms. )
[0078] [Chemical formula 3]
[0079]
[0080] (R 1 represents a hydrogen atom or a methyl group, R 4 represents a branched alkyl group having 3 or more carbon atoms.
[0081] In the above formula (2), R 3 The bonding position of is preferably any one of the hydrocarbons constituting the benzene ring. Examples of the monomer capable of forming the structural unit represented by the above formula (2) include styrene, α-methylstyrene, p-methylstyrene, and p-ethylstyrene.
[0082] In the above formula (3), R 4 The number of carbon atoms is preferably 3 to 10. Examples of the monomer capable of forming the structural unit represented by the formula (3) include isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate.
[0083] The content of the monomer (b) is preferably 20 mol% to 70 mol% relative to the total monomer components constituting the copolymer, more preferably 30 mol% to 70 mol%, and further preferably 40 mol% to 60 mol%. By adjusting the content of the monomer (b) within this range, a hydrophobic portion can be formed in the nonporous membrane to easily form a water-conducting path, and the moisture permeability is more excellent.
[0084] The above-mentioned thermoplastic resin may have a cationic portion in the above-mentioned hydrophilic portion and / or the above-mentioned hydrophobic portion, and may also have a cationic portion in other places. In addition, the above-mentioned thermoplastic resin preferably has a cationic portion in the hydrophilic portion. The above-mentioned cationic portion is preferably a cationic functional group or a group that can generate a cationic functional group. The above-mentioned group that can generate a cationic functional group refers to a group that does not have a cationic functional group at the stage of the above-mentioned thermoplastic resin, and generates a cationic functional group at the stage of forming the above-mentioned non-porous membrane and when used. In addition, the above-mentioned cationic functional group may also be a zwitterionic functional group that has both cations and anions. Therefore, the above-mentioned thermoplastic resin may have an anionic portion. In addition, the above-mentioned thermoplastic resin preferably does not have an anionic portion.
[0085] As the above-mentioned cationic functional group, for example, a nitrogen-containing group can be listed. As the above-mentioned nitrogen-containing group, a group containing ammonium ions or a group capable of forming ammonium ions can be listed. Here, the above-mentioned group capable of forming ammonium ions refers to a group that is not ionized at the stage of the above-mentioned thermoplastic resin, and forms an ionized body at the stage of forming the above-mentioned non-porous membrane and when used. As the above-mentioned group containing ammonium ions and the group capable of generating ammonium ions, for example, cyclic groups containing nitrogen atoms such as primary amino groups, secondary amino groups, tertiary amino groups, quaternary ammonium groups, imino groups (-NH- groups and =NH groups), amidine groups, imino groups, hydrazine groups, amide groups, imide groups, pyridyl groups, etc. can be listed. In addition, as the above-mentioned zwitterionic functional group, for example, a quaternary ammonium-containing group can be listed. As the above-mentioned quaternary ammonium-containing group, for example, a betaine group, a phosphorylcholine group, etc. can be listed. Among the above thermoplastic resins, from the viewpoint of exerting antibacterial properties and preventing bacteria from scattering from the nonporous film, groups capable of generating ammonium ions after the nonporous film is formed are preferred, and groups capable of generating quaternary ammonium groups (quaternary ammonium groups, imide groups) are more preferred.
[0086] When the thermoplastic resin is the copolymer, the copolymer preferably contains a structural unit derived from a monomer having a cationic functional group in a side chain. Examples of the monomer having a cationic functional group include monomers having the nitrogen-containing group as a functional group. Examples of the monomer having the nitrogen-containing group as a functional group include amide group-containing monomers, amino group-containing monomers, and imide group-containing monomers. Examples of the amide group-containing monomer include: N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, N,N-di(n-butyl) (meth)acrylamide, N,N-di(tert-butyl) (meth)acrylamide and the like N,N-dialkyl (meth)acrylamide; N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, N-n-butyl (meth)acrylamide and the like N-alkyl (meth)acrylamide; N-vinylacetamide, N-(2-hydroxyethyl) (meth)acrylamide, N- N-hydroxyalkyl (meth)acrylamide such as amine, N-(2-hydroxypropyl) (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, and N-(4-hydroxybutyl) (meth)acrylamide; N-alkoxyalkyl (meth)acrylamide such as N-methoxymethyl (meth)acrylamide, N-methoxyethyl (meth)acrylamide, and N-butoxymethyl (meth)acrylamide; and N,N-dimethylaminopropyl (meth)acrylamide and N-(meth)acryloyl morpholine. In addition, examples of amino group-containing monomers include substituted or unsubstituted amino group-containing (meth)acrylates such as aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate. In addition, examples of monomers containing an imide group include N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, N-(meth)acryloyl-8-oxyhexamethylene succinimide, N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, and N-laurylitaconimide. The above monomers having a cationic functional group may be used alone or in combination of two or more.
[0087] The content of the monomer having a cationic functional group is preferably 0.5 mol% to 10 mol%, more preferably 1 mol% to 7 mol%, and further preferably 2 mol% to 5 mol% relative to all monomer components constituting the copolymer. By adjusting the content of the monomer having a cationic functional group within this range, repulsion with scale components can be exerted, and adhesion / accumulation of scale components to the non-porous membrane can be suppressed.
[0088] In addition, the above-mentioned copolymer may also contain a structural part derived from a crosslinking agent. As the above-mentioned crosslinking agent, as long as it is a compound that can be crosslinked with the side chain of the monomer constituting the above-mentioned copolymer, there is no particular limitation. For example, a difunctional body preferably has two reactive functional groups. From the viewpoints of increasing the width of the density of the crosslinking density in the polymer, adjusting the mechanical properties, etc., a trifunctional or higher crosslinking agent can be used. As the above-mentioned crosslinking agent, for example, difunctional or higher epoxy-containing compounds, difunctional or higher isocyanate-containing compounds, etc. can be listed. In the above-mentioned copolymer, from the aspect of being able to generate quaternary ammonium ions after the crosslinking reaction with the functional group formed in the side chain, it is particularly preferred to contain difunctional or higher epoxy-containing compounds.
[0089] Examples of the epoxy group-containing compound include bisphenol A and epichlorohydrin-type epoxy compounds, polyethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, diglycidyl aniline, N,N,N',N'-tetraglycidyl-m-xylene diamine (e.g., trade name "TETRAD-X", manufactured by Mitsubishi Gas Chemical Co., Ltd.), and 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (e.g., trade name "TETRAD-C", manufactured by Mitsubishi Gas Chemical Co., Ltd.).
[0090] The amount of the crosslinking agent used is preferably 1 to 60 mol parts relative to the total amount (100 mol parts) of the reactive side chains of the copolymer, more preferably 2 to 30 mol parts, and further preferably 4 to 15 mol parts. By adjusting the amount of the crosslinking agent used within this range, a water-conducting path can be easily formed in the nonporous membrane, making it easy to make the moisture permeability excellent.
[0091] The weight average molecular weight of the thermoplastic resin is not particularly limited, but is preferably 20,000 to 2,000,000, more preferably 30,000 to 1,500,000, further preferably 50,000 to 1,000,000, and particularly preferably 70,000 to 500,000. The weight average molecular weight is a value calculated based on polystyrene conversion by gel permeation chromatography (GPC).
[0092] The non-porous film may also contain other components other than the thermoplastic resin within the range of not damaging the effect in the humidification laminate of the present disclosure. As the other components, for example, preservatives, anti-blocking agents, release agents, leveling agents, etc. can be listed. As the content of the other components, it is preferably 0.1 to 10 parts by mass relative to the total amount (100 parts by mass) of the copolymer, more preferably 0.15 to 3 parts by mass, and particularly preferably 0.2 to 2 parts by mass.
[0093] The above-mentioned non-porous membrane preferably has a structure in which the hydrophilic part and the hydrophobic part are separated on the surface due to the above-mentioned copolymer having a hydrophilic part and a hydrophobic part. The maximum diameter of the hydrophilic part in the above-mentioned non-porous membrane surface is preferably less than 50nm, more preferably less than 20nm. If the maximum diameter of the above-mentioned hydrophilic part is less than 50nm, the material with a size exceeding 50nm is not easy to penetrate the above-mentioned non-porous membrane, and the above-mentioned non-porous membrane can be used as a barrier film (barrier film) that does not allow materials (such as viruses, etc.) above 50nm to penetrate. The diameter of the above-mentioned hydrophilic part is evaluated by the following method. By using the adhesion measurement mode of a scanning probe microscope (SPM), the part with high adsorption force (hydrophilic part) and the part with low adsorption force (hydrophobic part) are digitized by adhesion, and processed using image analysis software, the diameter of the hydrophilic part can be calculated in the form of equivalent circle diameter. In addition, the above-mentioned maximum diameter is the diameter with the largest diameter in the diameter (equivalent circle diameter) of the hydrophilic part calculated as described above.
[0094] It should be noted that in the present disclosure, the structure in which the maximum diameter of the hydrophilic portion is below 50nm does not penetrate components of a size above 50nm, and therefore substantially only permeates water vapor, so the pores of the nonporous membrane in the present disclosure do not include pores below 50nm formed in the hydrophilic portion. In addition, when the maximum diameter of the hydrophilic portion exceeds 50nm, there is a possibility of permeating other components other than water vapor, and therefore a membrane having a structure in which the maximum diameter of a plurality of the hydrophilic portions exceeds 50nm is defined as a porous membrane.
[0095] The non-porous film is preferably a layer formed by coating. Since it is formed by coating, it can be easily made into a non-porous film, and it is easy to suppress the scattering of scale components, bacteria, etc.
[0096] <Porous reinforcement material>
[0097] Preferably, the porous reinforcing material is an element that serves as a support for the nonporous membrane and has excellent moisture permeability.
[0098] As the material forming the above-mentioned porous reinforcing material, any one of hydrophilic material and hydrophobic material can be used, but hydrophobic material is preferably used.If the above-mentioned hydrophobic material is used, when the composition for forming a non-porous film is applied, the composition does not penetrate into the porous reinforcing material, so in the porous reinforcing material, there is no need to prevent the guiding substrate from flowing down from the face opposite to the film forming face.
[0099] As the material forming the above-mentioned porous reinforcing material, for example, can be listed: organic matter such as polyolefin resin, cellulose resin, polycarbonate resin, polyamide resin, polyimide resin, polyamide-imide resin and fluorine resin, inorganic matter such as metal, glass and ceramic etc.Wherein, because the above-mentioned non-porous film can be made into film with lower temperature on the above-mentioned porous reinforcing material, in addition, from the viewpoint of excellent moisture permeability and water resistance, it is preferably organic matter, as the above-mentioned organic matter, it is particularly preferably polyolefin resin.The above-mentioned material can also be fibrous such as metal fiber, inorganic fiber.The material forming the above-mentioned porous reinforcing material can be only one kind, can also be two or more.
[0100] Examples of the porous reinforcing material include a resin porous film, an inorganic porous film, a metal porous film, and a fibrous substrate.
[0101] The polyolefin resin is a polymer (including an olefin elastomer) composed of an olefin as an essential monomer component, that is, a polymer containing at least a structural unit derived from an olefin in a molecule (in one molecule). The olefin is not particularly limited, and examples thereof include α-olefins such as ethylene, propylene, 1-butene, and 4-methyl-1-pentene.
[0102] Examples of the polyolefin resin include polymers containing ethylene as an essential monomer component (polyethylene resins), polymers containing propylene as an essential monomer component (polypropylene resins), ionomers, and amorphous cyclic olefin polymers.
[0103] The porosity of the porous reinforcing material is not particularly limited, but is preferably 30% to 90% by volume, more preferably 40% to 70% by volume. If the porosity is 30% by volume or more, the moisture permeability becomes better. If the porosity is 90% by volume or less, the supporting performance of the nonporous membrane becomes better.
[0104] The thickness of the porous reinforcing material is not particularly limited, but from the viewpoint of fully supporting the nonporous film, it is preferably more than 5 μm, more preferably more than 10 μm. In addition, considering excellent moisture permeability and economy, the thickness of the porous reinforcing material is preferably less than 50 μm, more preferably less than 30 μm.
[0105] From the viewpoint of being able to easily form the nonporous film, the surface of the porous reinforcing material on the side having the nonporous film (for example, Figure 1 The surface 11a shown in (11) is preferably hydrophilized. Particularly, when a hydrophobic material is used as the material forming the above-mentioned porous reinforcing material, the above-mentioned hydrophilization is preferably implemented. As the above-mentioned hydrophilization, corona discharge treatment, plasma treatment, etc. can be listed. Through these hydrophilization, carboxyl, hydroxyl or carbonyl can be generated on the porous reinforcing material surface, and the composition used to form the above-mentioned non-porous film is easily wetted and expanded on the porous reinforcing material surface, and the above-mentioned non-porous film is easily formed. In addition, thus, the adhesion of the above-mentioned porous reinforcing material and the above-mentioned non-porous film is improved. In addition, when the above-mentioned porous reinforcing material formed by the hydrophobic substrate is kept as a winding body, the form in which one face of the above-mentioned porous reinforcing material contacts with the other face in the winding body, but because a hydrophilic face contacts with the hydrophobic other face, adhesion can be prevented.
[0106] The surface tension of the surface of the porous reinforcing material on one side of the non-porous film is preferably 35dyn / cm to 55dyn / cm, and more preferably 37dyn / cm to 50dyn / cm. If the surface tension is 35dyn / cm or more, it is easy to apply the composition for forming the non-porous film, and it is easy to form the non-porous film. If the surface tension is 55dyn / cm or less, the composition for forming the non-porous film can not be excessively wetted and expanded, and the non-porous film can be easily formed on the surface of the porous reinforcing material. It should be noted that when the surface of the porous reinforcing material is hydrophilized, the surface on one side of the non-porous film is the surface to which the hydrophilization treatment is applied.
[0107] The surface tension of the inside of the above-mentioned porous reinforcing material (that is, the inside of the region where the above-mentioned non-porous film is not formed) is preferably less than 35dyn / cm, more preferably less than 33dyn / cm. If the above-mentioned surface tension is less than 35dyn / cm, the composition for forming the above-mentioned non-porous film can be suppressed from penetrating into the inside of the above-mentioned porous reinforcing material, and the above-mentioned non-porous film is easily formed on the surface of the above-mentioned porous reinforcing material. It should be noted that, when the surface of the above-mentioned porous reinforcing material has been hydrophilized, the inside of the above-mentioned porous reinforcing material is the inside of the region where the hydrophilization treatment is not implemented. In addition, the surface tension of the above-mentioned inside can be obtained by measuring the cross section obtained by cutting off the above-mentioned porous reinforcing material.
[0108] The water content of the porous reinforcing material at a relative humidity of 100% is preferably 0.01% to 0.5%, more preferably 0.05% to 0.4%, and particularly preferably 0.1% to 0.3%. From the viewpoint of making the water content of the non-porous membrane 10 times or more of the porous reinforcing material, the water content of the porous reinforcing material at a relative humidity of 100% is preferably within the above range.
[0109] The adsorption isotherm of the porous reinforcing material is preferably any one of Type I to Type VI shown in IUPAC, and more preferably Type III. By making the adsorption isotherm of the porous reinforcing material any one of Type I to Type VI shown in IUPAC, the water retention capacity of the non-porous membrane tends to increase, so it is easy to exert moisture permeability.
[0110] The moisture permeability of the porous reinforcing material is preferably 1350 g / (m 2 ·24h) or less, more preferably 1000g / (m 2 24h) or less.
[0111] The porous reinforcing material preferably has a moisture permeability of 18000 g / (m 2 ·24h) or less, more preferably 15000g / (m 2 ·24h) or less, more preferably 10000g / (m 2 24h) or less.
[0112] The moisture permeability of the humidifying laminate is preferably more than 1350 g / (m 2 ·24h), more preferably 1370g / (m 2 The above-mentioned humidifying laminate has excellent moisture permeability, so the above-mentioned moisture permeability can exceed 1350g / (m 2 ·24h) structure.
[0113] The moisture permeability of the humidifying laminate is preferably more than 18000 g / (m 2 ·24h), more preferably 19000g / (m 2·24h) or more, more preferably 20000g / (m 2 The above-mentioned humidifying laminate has excellent moisture permeability, so the above-mentioned moisture permeability can be more than 18000g / (m 2 ·24h) structure.
[0114] In addition, the difference in moisture permeability between the humidifying laminate and the porous reinforcing material alone is preferably 0 g / (m 2 ·24h) or more, more preferably 10g / (m 2 ·24h) or more, particularly preferably 30g / (m 2 ·24h) or more.
[0115] In addition, the difference in moisture permeability between the humidifying laminate and the porous reinforcing material alone is preferably 0 g / (m 2 ·24h) or more, more preferably 1000g / (m 2 ·24h) or more, particularly preferably 2000g / (m 2 ·24h) or more.
[0116] The thickness of the humidifying laminate is not particularly limited, but is preferably 5.5 μm to 55 μm, and more preferably 7 μm to 30 μm. When the thickness of the humidifying laminate is 5.5 μm or more, moisture permeability is easily exerted, and when the thickness of the humidifying laminate is 55 μm or less, economic efficiency is excellent and miniaturization is easy when used in a humidifier.
[0117] [Method for producing a humidifying laminate]
[0118] The disclosed humidification laminate can be made by forming the above-mentioned non-porous film using a known or customary method on at least one surface of the above-mentioned porous reinforcing material.For example, the above-mentioned non-porous film can be directly formed on a surface of the above-mentioned porous reinforcing material, or after the above-mentioned non-porous film is temporarily formed on other supports, transfer (lamination) is applied to a surface of the above-mentioned porous reinforcing material, thus forming the above-mentioned non-porous film on the porous reinforcing material.Wherein, from the viewpoint of the excellent adhesion of the above-mentioned non-porous film and the above-mentioned porous reinforcing material, the method of the former is preferably used.
[0119] The surface of the porous reinforcing material on the side where the nonporous membrane is provided may be subjected to a hydrophilic treatment. Examples of the hydrophilic treatment include the above-mentioned treatments.
[0120] The nonporous film can be formed by coating (applying) the composition for forming the nonporous film onto the porous reinforcing material or the other support, and removing the solvent from the obtained coating film by heating or the like.
[0121] Since the porous reinforcing material is subjected to the hydrophilization treatment to suppress blocking, it can be produced by a roll-to-roll method in which a non-porous film is formed on the porous reinforcing material previously made into a rolled body and then the rolled body is made again.
[0122] The above-mentioned composition can be made by a known or customary method. For example, the above-mentioned copolymer can be made by dissolving or dispersing it in a solvent, and mixing additives such as preservatives as needed. As the above-mentioned solvent, water and / or a water-soluble solvent are preferred. It can be inferred that when water or a water-soluble solvent is used, the above-mentioned copolymer is dispersed in the composition in a core-shell shape with the inner side being the hydrophobic portion and the outer side being the hydrophilic portion. By using such a composition, the hydrophilic portion is separated from the hydrophobic portion when the coating is dried, and a non-porous film is formed in a state with a water-conducting channel. In addition, it can be inferred that the hydrophobic portion becomes a state of being firmly bonded to each other, and water resistance becomes better.
[0123] Examples of the water-soluble solvent include aliphatic water-soluble alcohols such as methanol, ethanol, n-propanol, and isopropanol; glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, and propylene glycol monoethyl ether; and the like. The water-soluble solvent may be used alone or in combination of two or more.
[0124] The ratio (concentration) of the above-mentioned copolymer in the above-mentioned composition in which the above-mentioned copolymer is dissolved or dispersed is not particularly limited, and is preferably 0.5 to 5% by mass, more preferably 1 to 4% by mass, and further preferably 1.5 to 3% by mass. If the above-mentioned concentration is less than 5% by mass, the thickness of the coating layer thickens, so the film thickness of the non-porous film after drying is further uniformized. Thus, a non-porous film with excellent gas barrier properties and further thin filmization can be formed, and as a result, moisture permeability is further improved. In addition, if the above-mentioned concentration is within the above-mentioned range, the coating property is excellent, and in addition, a non-porous film with excellent moisture permeability and gas barrier properties is easily formed.
[0125] It should be noted that the coating (applying) of the above-mentioned composition can also utilize known coating methods. For example, coating machines such as gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, bar coater, knife coater, spray coater, comma coater, direct coater, etc. can also be used. Formed by such coating, thus easily form a non-porous film.
[0126] The heating temperature when the above-mentioned coating film is desolvated is preferably 35°C to 90°C, more preferably 40°C to 85°C, and further preferably 45°C to 80°C. The heating time can be appropriately used for an appropriate time, for example, 5 seconds to 20 minutes, preferably 5 seconds to 10 minutes, and more preferably 10 seconds to 5 minutes. The above-mentioned composition can be used to form a non-porous film at a low temperature below 90°C (especially below 80°C), so it is easy to form a film. In addition, a polyolefin resin with excellent moisture permeability can be used as a porous reinforcing material.
[0127] The humidifying laminated body in which the non-porous film is formed on at least one surface of the porous reinforcing material by the above method has excellent moisture permeability, and the shape of the humidifier can be miniaturized. It should be noted that the humidifying laminated body refers to a laminated body that enables water vapor to move through the humidifying laminated body. In addition, the humidifying laminated body has a structure in which the hydrophilic part and the hydrophobic part are separated, so it can also be used as a barrier film with moisture permeability. In the case where the diameter of the hydrophilic part is small, since it is a barrier film with the above moisture permeability, a small-sized substance (such as water vapor) with hydrophilicity is allowed to pass through the hydrophilic part, and a large-sized substance (such as a virus) is not allowed to pass through the hydrophilic part, thereby separating the two.
[0128] Furthermore, the humidifying laminate can be thinner than conventional moisture-permeable films, and therefore, when used in a humidifier, the shape itself can be miniaturized, and the economic efficiency is also excellent.
[0129] [Bag-shaped water-retaining container]
[0130] By covering the outside of the frame with the humidification laminate, a bag-shaped water-retaining container can be produced.
[0131] The frame is preferably made of a rigid material, such as resin, metal / alloy material, etc. In addition, the frame may be a plate-shaped or bag-shaped frame produced by extrusion molding, a plate-shaped frame produced by injection molding, or a bag-shaped structure produced by laminating two or more plate-shaped frames. In addition, the hole portion may be provided after the bag-shaped frame is produced, or a frame with the hole portion provided in advance may be produced.
[0132] Preferably, a part or the whole of the contact portion between the laminate and the frame is bonded. The method of bonding to the frame is not particularly limited, and the laminate can be bonded by bonding using a known or commonly used adhesive, or by welding using ultrasonic welding, high-frequency welding, thermal welding, or the like.
[0133] The above method can be used to make a bag-shaped water-retaining container. The bag-shaped water-retaining container has a stacked body arranged outside a frame structure, and the water of the liquid introduced into the bag-shaped water-retaining container is absorbed by the stacked body as water vapor, diffuses in the stacked body, and can release water vapor from the entire stacked body.
[0134] In addition, a humidifier can be manufactured by mounting a plurality of the bag-shaped water-retaining containers. Such a humidifier has improved humidification performance compared to the past, so it can achieve the same performance while miniaturizing the humidifier, and is also excellent in terms of cost.
[0135] Therefore, the humidifier includes the humidifying laminate, and thus the moisture permeability is improved, so that the humidifier can be reduced in size, and thus can be suitably used for applications such as air conditioners, ventilators, and air purifiers.
[0136] Each scheme disclosed in this specification may also be combined with any other feature disclosed in this specification. Each configuration and combination of configurations in each embodiment is an example, and appropriate addition, omission, substitution and other changes of configurations may be made within the scope of the present disclosure. In addition, each invention disclosed in this disclosure is not limited by the embodiments and the following examples, but only by the patent claims.
[0137] Example
[0138] Hereinafter, one embodiment of the present disclosure will be described in more detail based on examples.
[0139] Example 1
[0140] 100 parts by mass of thermoplastic resin solution was diluted with 22 parts by mass of ethanol and 143 parts by mass of distilled water to prepare a coating solution with a resin concentration of 10% by mass. The thermoplastic resin solution contained: 47 parts by mass of isobutyl acrylate and 1 part by mass of styrene as structural units forming the hydrophobic part in the polymer; 21 parts by mass of acrylic acid and 28 parts by mass of methyl acrylate as structural units forming the hydrophilic part; 3 parts by mass of imide as structural units forming the cationic part; and 2 parts by mass of epoxy compound as a crosslinking agent. On the other hand, one surface of a porous substrate made of polypropylene resin (thickness: 20 μm, porosity: 48% by volume) was corona treated to form a hydrophilic surface with a surface tension of 39 dyn. Then, the above composition was applied to the hydrophilic surface of the above porous reinforcing material using a wire rod, and heated at 70°C for 1 minute to form a non-porous film (thickness: 1 μm). In this way, a humidifying laminate of Example 1 was produced.
[0141] Embodiment 2-3
[0142] The humidifying laminates of Examples 2 and 3 were prepared in the same manner as in Example 1 except that the thickness of the nonporous film was changed.
[0143] [evaluate]
[0144] The humidifying laminates obtained in the Examples and Comparative Examples were evaluated as follows. The evaluation results are shown in the table. In addition, a porous polypropylene resin substrate itself, on which no nonporous film was formed, was evaluated as Comparative Example 1.
[0145] (1) Moisture permeability
[0146] For the humidifying laminates obtained in the examples and comparative examples, the moisture permeability was measured based on the moisture permeability test method (cup method) of JIS Z0208-1976. Specifically, the humidifying laminates obtained in the examples and comparative examples were left to stand in the measurement environment for more than 2 hours, and then covered with the above-mentioned moisture permeable cup as a moisture permeable sheet to make it airtight. Then, a moisture permeable cup with 40g of water added was placed in a constant temperature and humidity chamber under the environment of temperature 20°C, relative humidity 30%, and wind speed 2.4m / s, and the total mass reduction of water and moisture permeable cup after 1 hour was converted into the test piece per 1m 2 The mass after 24 hours was calculated as the moisture permeability. In addition, the moisture permeability was also measured under the same conditions at a temperature of 20°C, a relative humidity of 65%, and in an environment with virtually no wind (wind speed of 0.1 m / s).
[0147] (2) Moisture content
[0148] The moisture content of each humidifying laminate obtained in Examples and Comparative Examples was measured by a water vapor adsorption method.
[0149] [Table 1]
[0150] (Table 1)
[0151]
[0152] As shown in the results of Examples 1 to 3, it was confirmed that the humidifying laminate of the present disclosure has a moisture permeability higher than that of the porous reinforcing material alone shown in Comparative Example 1 due to the nonporous membrane. It was also confirmed that the moisture permeability increased as the nonporous membrane became thicker.
[0153] Modifications of the invention disclosed herein will be described below.
[0154] [Note 1]
[0155] A humidifying laminate, comprising: a porous reinforcing material; and a non-porous film laminated on at least one surface of the porous reinforcing material and functioning as a moisture-permeable film, wherein the moisture permeability of the laminate is greater than that of the porous reinforcing material alone.
[0156] [Note 2]
[0157] The humidifying laminate according to Supplementary Note 1, wherein the nonporous film has a property that the water vapor permeability increases as the film thickness increases.
[0158] [Note 3]
[0159] The humidifying laminate according to Supplementary Note 1 or 2, wherein the adsorption isotherm of the porous reinforcing material is any one of Types I to VI indicated by IUPAC.
[0160] [Note 4]
[0161] The humidifying laminate according to any one of Supplementary Notes 1 to 3, wherein the adsorption isotherm of the porous reinforcing material is type III according to IUPAC.
[0162] [Note 5]
[0163] The humidifying laminate according to any one of Appendixes 1 to 4, wherein the adsorption isotherm of the nonporous membrane is any one of types I to VI as indicated by IUPAC.
[0164] [Note 6]
[0165] The humidifying laminate according to any one of Appendixes 1 to 5, wherein the adsorption isotherm of the nonporous membrane is type III as indicated by IUPAC.
[0166] [Note 7]
[0167] The humidifying laminate according to any one of Appendixes 1 to 6, wherein the water content of the nonporous film at a relative humidity of 100% is 15 times or more the water content of the porous reinforcing material at a relative humidity of 100%.
[0168] [Note 8]
[0169] The humidifying laminate according to any one of Appendixes 1 to 7, wherein the nonporous membrane is disposed on the water side of the liquid with respect to the porous reinforcing material, and absorbs water from the liquid and releases it into the air.
[0170] [Note 9]
[0171] The humidifying laminate according to any one of Appendixes 1 to 8, wherein the nonporous film comprises a thermoplastic resin having a cationic portion, and the cationic portion contains a group containing an ammonium ion or a group capable of forming an ammonium ion.
[0172] [Note 10]
[0173] The humidifying laminate according to any one of Appendixes 1 to 9, wherein the thermoplastic resin has a hydrophilic portion, and the hydrophilic portion contains a structural unit represented by the following formula (1).
[0174] [Chemical formula 1]
[0175]
[0176] R 1 , R 2 Each independently represents a hydrogen atom or a methyl group.
[0177] [Note 11]
[0178] The humidifying laminate according to any one of Appendixes 1 to 10, wherein the thermoplastic resin has a hydrophobic portion, and the hydrophobic portion contains a structural unit represented by the following formula (2) and / or the following formula (3).
[0179] [Chemical formula 2]
[0180]
[0181] R 1 represents a hydrogen atom or a methyl group, R 3 It represents an alkyl group having 1 to 2 carbon atoms.
[0182] [Chemical formula 3]
[0183]
[0184] R 1 represents a hydrogen atom or a methyl group, R 4 It represents a branched alkyl group having 3 or more carbon atoms.
[0185] [Note 12]
[0186] The humidifying laminate according to any one of Appendixes 1 to 11, wherein the nonporous film is applied so as to cover at least one surface of the porous reinforcing material.
[0187] [Note 13]
[0188] A humidifier provided with a plurality of bag-shaped water-retaining containers formed by bonding the humidifying laminate according to any one of Supplementary Notes 1 to 12 to a frame.
[0189] [Note 14]
[0190] An air conditioner equipped with the humidifier according to Supplementary Note 13.
[0191] [Note 15]
[0192] A ventilation device equipped with the humidifier according to Supplementary Note 13.
[0193] [Note 16]
[0194] An air purifier equipped with the humidifier according to Supplementary Note 13.
[0195] Description of Reference Numerals
[0196] 1: laminate;
[0197] 11: Porous reinforcement material;
[0198] 11a: One surface of the porous reinforcement material;
[0199] 12: Non-porous membrane.
Claims
1. A humidifying laminate, comprising: a porous reinforcing material; and a non-porous film laminated on at least one surface of the porous reinforcing material and functioning as a moisture-permeable film, wherein: The moisture permeability of the laminate is equal to or higher than that of the porous reinforcing material alone.
2. The humidifying laminate according to claim 1, wherein The non-porous film has a property that the thicker the film, the higher the moisture permeability.
3. The humidifying laminate according to claim 1 or 2, wherein The adsorption isotherm of the porous reinforcing material is any one of types I to VI as indicated by IUPAC.
4. The humidifying laminate according to claim 1 or 2, wherein The adsorption isotherm of the porous reinforcing material is type III as shown by IUPAC.
5. The humidifying laminate according to claim 1 or 2, wherein The adsorption isotherm of the nonporous membrane is any one of types I to VI shown by IUPAC.
6. The humidifying laminate according to claim 1 or 2, wherein The adsorption isotherm of the non-porous membrane is type III as shown by IUPAC.
7. The humidifying laminate according to claim 1 or 2, wherein The moisture content of the nonporous film at a relative humidity of 100% is 10 times or more the moisture content of the porous reinforcing material at a relative humidity of 100%.
8. The humidifying laminate according to claim 1 or 2, wherein The non-porous membrane is disposed on the water side of the liquid relative to the porous reinforcing material, and is used to absorb water from the liquid and release it into the air.
9. The humidifying laminate according to claim 1 or 2, wherein The nonporous film includes a thermoplastic resin having a cationic portion containing a group including an ammonium ion or a group capable of forming an ammonium ion.
10. The humidifying laminate according to claim 1 or 2, wherein The thermoplastic resin has a hydrophilic portion, and the hydrophilic portion contains a structural unit represented by the following formula (1): [Chemical formula 1] In the formula, R1 and R2 independently represent a hydrogen atom or a methyl group.
11. The humidifying laminate according to claim 1 or 2, wherein The thermoplastic resin has a hydrophobic portion, and the hydrophobic portion contains a structural unit represented by the following formula (2) and / or the following formula (3), [Chemical formula 2] In formula (2), R1 represents a hydrogen atom or a methyl group, and R3 represents an alkyl group having 1 to 2 carbon atoms. [Chemical formula 3] In formula (3), R1 represents a hydrogen atom or a methyl group, and R4 represents a branched alkyl group having 3 or more carbon atoms.
12. The humidifying laminate according to claim 1 or 2, wherein The non-porous film is applied so as to cover at least one surface of the porous reinforcing material. 13 . A humidifier comprising a plurality of bag-shaped water-retaining containers formed by bonding the humidifying laminate according to claim 1 or 2 to a frame.
14. An air conditioner equipped with the humidifier according to claim 13.
15. A ventilation device equipped with the humidifier according to claim 13.
16. An air purifier equipped with the humidifier according to claim 13.
Citation Information
Patent Citations
Humidifying sheet
JP2001174008A
Quick lime manufacturing system
JP2022096876A
Gas-liquid separating element, gas-liquid separator, and gas-liquid separating unit
JP2003097831A
Laminate
WO2022070948A1